The Role of Cytokines Produced via the NLRP3 Inflammasome in Mouse Macrophages Stimulated with Dental Calculus in Osteoclastogenesis - Megumi Mae (MDPI AG, 2021)
Dental calculus (DC) is a common deposit in periodontitis patients. We have previously shown that DC contains both microbial components and calcium phosphate crystals that induce an osteoclastogenic cytokine IL-1β via the NLRP3 inflammasome in macrophages. In this study, we examined the effects of cytokines produced by mouse macrophages stimulated with DC on osteoclastogenesis. The culture supernatants from wild-type (WT) mouse macrophages stimulated with DC accelerated osteoclastogenesis in RANKL-primed mouse bone marrow macrophages (BMMs), but inhibited osteoclastogenesis in RANKL-primed RAW-D cells. WT, but not NLRP3-deficient, mouse macrophages stimulated with DC produced IL-1β and IL-18 in a dose-dependent manner, indicating the NLRP3 inflammasome-dependent production of IL-1β and IL-18. Both WT and NLRP3-deficient mouse macrophages stimulated with DC produced IL-10, indicating the NLRP3 inflammasome-independent production of IL-10. Recombinant IL-1β accelerated osteoclastogenesis in both RANKL-primed BMMs and RAW-D cells, whereas recombinant IL-18 and IL-10 inhibited osteoclastogenesis. These results indicate that DC induces osteoclastogenic IL-1β in an NLRP3 inflammasome-dependent manner and anti-osteogenic IL-18 and IL-10 dependently and independently of the NLRP3 inflammasome, respectively. DC may promote alveolar bone resorption via IL-1β induction in periodontitis patients, but suppress resorption via IL-18 and IL-10 induction in some circumstances.